Komunikasi Antarpribadi Guru Tari Kepada Murid Di Semarak Candrakirana Art Center (Studi Deskriptif Kualitatif Komunikasi Antarpribadi Guru Tari Kepada Murid Dalam Meningkatkan Kepercayaan Diri Di Semarak Candrakirana Art Center) - Rahmadiani, Iga Firdausy, Palupi, MA (2017)
Educational services should be conducted optimally to students who have intellegence and special talents. Teachers play important roles in learning process. Interpersonal relationship between teachers and students should be made in the pattern of communication, especially in the process of delivering materials, and it is not related only in determining contents, but also in determining relationship. Mastering interpersonal communication competency becomes very significant by the teachers in boosting students' motivation. This research aimed to know the interpersonal communication is made between teacher and students in increasing students' motivation. This research applied qualitative descriptive method using observation, in-depth interview, with determining appropriate strategy in collecting data in order to determine focus and data elaboration. The result of the study showed; (1) the teachers of Semarak Candrakirana Art Center had mastered basic skills of communication including the attitude of trusting, oppennes, support, and problem solver. (2) A teacher who had positive self-concept would instill positive things to the students such as trying new experiences, dare to success, being not afraid of failure,optimism, confidence, positive thinking, self-respect, and feeling enthuastic in reaching the goals. (3) Childern personality was constructed by things given by their parents. (4) In increasing confidence, teacher gave students motivation to keep developing their talents in dance field, such as sending them to the competition or events held by its own art center or the torism office. (5) Teachers' effort in boosting students confidence was done by persuading and convincing students that they could be better and could reach more achievement. The efforts were actualized by giving reward as the appreciation from teacher to the students' achievement.